2020
DOI: 10.1377/hlthaff.2020.00903
|View full text |Cite
|
Sign up to set email alerts
|

Staying Connected In The COVID-19 Pandemic: Telehealth At The Largest Safety-Net System In The United States

Abstract: New York City Health + Hospitals is the largest safety-net health care delivery system in the United States. Before the coronavirus disease 2019 (COVID-19) pandemic, NYC Health + Hospitals served more than one million patients annually, including the most vulnerable New Yorkers, while billing fewer than five hundred telehealth visits monthly. Once the pandemic struck, we established a strategy to allow us to continue to serve our existing patients while treating the surge of new patients. Starting in March 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
113
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(130 citation statements)
references
References 2 publications
2
113
0
Order By: Relevance
“…21,22 An Ontario pilot study of virtual care showed that, when provided with a choice of audio, video or text messaging on an integrated platform, more than 90% of visits occurred using asynchronous, secure text messaging followed by audio, yet there are no billing codes for text messaging. 28 Despite extensive use of virtual care in the COVID-19 pandemic, [23][24][25][26][27] the appropriate role of virtual care remains to be determined. It is not possible to separate the role of physician funding for virtual care from the impact of the pandemic itself in the major uptake of virtual care.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 An Ontario pilot study of virtual care showed that, when provided with a choice of audio, video or text messaging on an integrated platform, more than 90% of visits occurred using asynchronous, secure text messaging followed by audio, yet there are no billing codes for text messaging. 28 Despite extensive use of virtual care in the COVID-19 pandemic, [23][24][25][26][27] the appropriate role of virtual care remains to be determined. It is not possible to separate the role of physician funding for virtual care from the impact of the pandemic itself in the major uptake of virtual care.…”
Section: Discussionmentioning
confidence: 99%
“…While the number of telehealth visits has increased during the pandemic [23] and international oncology guidelines suggest that telemedicine needs to be considered to support patients and reduce oncology patients' exposure to COVID-19 [24], little is known about how oncology patients have accessed healthcare during the pandemic. As shown in Table 2, only 20.3% of our sample contacted their primary care provider and only 10.4% contacted their oncologist.…”
Section: Discussionmentioning
confidence: 99%
“…While our system has benefited from the growth of telemedicine to communicate virtually with patients in their homes, care spaces similarly will be outfitted with telecommunication technology to transform the nature of onsite care delivery. 6 Starting with isolation rooms, video monitoring and communication devices will allow for virtual POST-COVID-19, PRE-VACCINE EMERGENCY PREPAREDNESS encounters to limit direct contact, avoiding unnecessary use of personal protective equipment and protecting staff who do not need to assess the patient at the bedside, including registration clerks, financial counselors, and social workers. In one emergency department, this same technology was used to screen patients at the entrance doors, allowing for rapid direction to the most appropriate area of the department.…”
Section: Incorporate New Distancing Into Care Spacesmentioning
confidence: 99%